2012
DOI: 10.1021/jf302896m
|View full text |Cite
|
Sign up to set email alerts
|

Tentative Identification of Phenolic Compounds in Olive Pomace Extracts Using Liquid Chromatography–Tandem Mass Spectrometry with a Quadrupole–Quadrupole-Time-of-Flight Mass Detector

Abstract: The reuse of agronomical residues is a pending goal for sustainable agriculture. Particular residues in olive-oil-producing countries are leaves, wastewater, and olive pomace. Olive leaves and wastewaters have been previously characterized by isolation of the phenolic fraction. However, olive pomace has not yet been qualitatively characterized as a source of phenols. Olive pomace extracts were obtained using superheated solvent extraction using 50:50 (v/v) water/ethanol as a leaching mixture at 160 °C. The ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 38 publications
8
55
0
1
Order By: Relevance
“…This type of monoterpenes is widely spread in Oleaceae (Obied et al, ). It should be mentioned that their fragmentation patterns were in accordance with previous works (Peralbo‐Molina et al, ; Pérez‐Bonilla et al, ; Hashmi et al, ; Michel et al, ), in which the presence of these iridoids was reported in olive wood and leaves. As an example, Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This type of monoterpenes is widely spread in Oleaceae (Obied et al, ). It should be mentioned that their fragmentation patterns were in accordance with previous works (Peralbo‐Molina et al, ; Pérez‐Bonilla et al, ; Hashmi et al, ; Michel et al, ), in which the presence of these iridoids was reported in olive wood and leaves. As an example, Fig.…”
Section: Resultssupporting
confidence: 91%
“…(A) shows the fragmentation pattern of loganic acid glucoside, which was characterised by the consecutive loss of two glucose moieties and CO 2 for yields: the product ions at m/z 375.13, 213.08 and 169.08, respectively. In addition, the products' ions obtained at m/z 151.08 (C 9 H 11 O 2 ) and 113.02 (C 5 H 5 O 3 ) were characteristic fragments for identification of loganic acid according to Peralbo‐Molina et al ().…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, in Conservolea brines, the presence of oleoside was recorded only in MIX and LY brines after 14 and 63 days of fermentation, respectively. The compound eluted at 17.7 min in the Conservolea brine samples described in the literature for oleoside 11‐methyl ester was identified in Conservolea brines of all treatments after 14 days of fermentation and was detectable only in the LY brine until day 63 of fermentation (data not shown). Oleoside, hydroxylated product of decarboxymethyl elenolic acid, hydroxytyrosol acyclodihydroelenolate, caffeoyl‐6‐secologanoside and 6′‐ p ‐coumaroyl secologanoside (comselogoside) were identified in olive‐mill wastewaters in a previous work from our group, where the fragmentation pattern of these compounds is given in detail .…”
Section: Resultssupporting
confidence: 74%
“…Extraction of phenols from alperujo can be based on contact of the semisolid residue with the extractant (usually water or, better, an ethanol-water mixture if the extract is for edible uses); or a methanol-water mixture if only analytical information is the aim of extraction. Acceleration of the extraction step can be achieved by assisting it with auxiliary energies such as ultrasound [68], microwaves [69], or high temperature + pressure [70]. The extracts thus obtained have been used for enrichment of refined edible oils that improve their stability and healthy properties in this way [69].…”
Section: Partial Use Of Either Alpechín or Alperujomentioning
confidence: 99%